‘Effects of a home-based bimodal lifestyle intervention in frail patients with end-stage liver disease awaiting orthotopic liver transplantation’: study protocol of a non-randomised clinical trial - Hans Blokzijl; Vincent E de Meijer; Rienk Dekker; Joost M Klaase; Coby Annema; Bart C Bongers; Allard G Wijma; Job AM van der Palen; Frans JC Cuperus (BMJ Open)
Introduction Patients with end-stage liver disease awaiting orthotopic liver transplantation (OLT) are generally classified as frail due to disease-related malnutrition and a progressive decline in musculoskeletal and aerobic fitness, which is associated with poor pre-OLT, peri-OLT and post-OLT outcomes. However, frailty in these patients may be reversable with adequate exercise and nutritional interventions.Methods and analysis Non-randomised clinical trial evaluating the effect of a home-based bimodal lifestyle programme in unfit patients with a preoperative oxygen uptake (VO2) at the ventilatory anaerobic threshold ≤13 mL/kg/min and/or VO2 at peak exercise ≤18 mL/kg/min listed for OLT at the University Medical Center Groningen (UMCG). The programme is patient tailored and comprises high-intensity interval and endurance training, and functional exercises three times per week, combined with nutritional support. Patients will go through two training periods, each lasting 6 weeks.The primary outcome of this study is the impact of the programme on patients’ aerobic fitness after the first study period. Secondary outcomes include aerobic capacity after the second study period, changes in sarcopenia, anthropometry, functional mobility, perceived quality of life and fatigue, incidence of hepatic encephalopathy and microbiome composition. Moreover, number and reasons of intercurrent hospitalisations during the study and postoperative outcomes up to 12 months post OLT will be recorded. Finally, feasibility of the programme will be assessed by monitoring the participation rate and reasons for non-participation, number and severity of adverse events, and dropout rate and reasons for dropout.Ethics and dissemination This study was approved by the Medical Research Ethics Committee of the UMCG (registration number NL83612.042.23, August 2023) and is registered in the Clinicaltrials.gov register (NCT05853484). Good Clinical Practice guidelines and the principles of the Declaration of Helsinki will be applied. Results of this study will be submitted for presentation at (inter)national congresses and publication in peer-reviewed journals.Trial registration number NCT05853484.